Economic Selection of Generators for a Wind Farm - Omid Alavi; Behzad Vatandoust (IAES Indonesian Section, 2015)
The selection suitable generator for wind turbines will be done based on technical criteria and priorities of the project. In this paper, a method for determining the type of wind turbine generator with an example is explained. In the paper, for a 10kW wind turbine, two generators have been proposed. The first case is a squirrel-cage asynchronous generator coupled to the turbine through the gearbox and directly connected to three phase output. Other PM generators that are directly coupled to the turbine and it is connected to the grid using the inverter. The results show that according to wind conditions, a 10kW permanent magnet generator is more advantageous in terms of energy production.